THE SPECIES ACANTHOLIMON ZAKIROVII, ACANTHOLIMON SUBAVENACEUM, AND ACANTHOLIMON SUBAVENACEUM, WHOSE NATURAL POPULATIONS ARE EXPANDING IN THE NUROTA BOTANICAL-GEOGRAPHICAL DISTRICT (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The article presents information about the species Acantholimon zakirovii, Acantholimon subavenaceum, and Acantholimon subavenaceum, whose natural populations are expanding in the Nurota botanical-geographical district.